Evaluation of the Effects of Delayed Cord Clamping in Infants of Diabetic Mothers - Korkut, Sabriye; Oğuz, Yüksel; Bozkaya, Davut; Türkmen, Gülenay Gençosmanoğlu; Kara, Özgür; Uygur, Dilek; Oğuz, Şerife Suna (American Journal of Perinatology, 2019)
Objective This study aimed to investigate the effect of delayed cord clamping (DCC) in infants of diabetic mothers.Study Design Women who had diabetes throughout their pregnancy and gave birth at 37 weeks of gestation or later were included in the study along with their babies. Early cord clamping was performed as soon as possible after birth, while DCC was performed by clamping 60 second after birth. The two groups were compared in terms of venous hematocrit (htc) levels and rates of hypoglycemia, jaundice requiring phototherapy, and respiratory distress.Results Venous htc levels at postnatal 6 and 24 hours were significantly higher in the DCC group (p = 0.0001). Polycythemia rates were higher in the DCC group at both 6 and 24 hours, but partial exchange transfusion (PET) was not needed in either group. There were no differences between the groups with regard to the rates of hypoglycemia or jaundice requiring phototherapy. Rate of admission to the neonatal intensive care unit (NICU) was lower in the DCC group.Conclusion Although DCC increased the rate of polycythemia, it did not result in PET requirement. Moreover, DCC reduced the severity of respiratory distress and the rate of admission to NICU due to respiratory distress.
Keywords: delayed cord clamping; term; infant of diabetic mother; polycythemia; respiratory distress